CLASSICAL ASHTAVAIDYAN AYURVEDIC THERAPY IN THE FUNCTIONAL IMPROVEMENT OF PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: CASE STUDY - Neelakandhan Mooss, Ashtavaidyan ET; Kumar S, *Sudeesh; Krishnan N, Navaneeth; PB, Smina; Nair, PKS (International Journal of Ayurveda and Pharma Research, 2019)
Background: Systemic lupus erythematosus is a systemic auto immune connective tissue disease that can affect any part of the body. The disease has no direct reference in Ayurvedic texts. Considering the symptomatology, it can be compared with Upadrava of Vatarakta. Methodology: In this study, 3 patients (age group between 15– 60 yrs) diagnosed SLE with the help of ACR criteria after assessing both objective and subjective parameters have undergone the prescribed classical Ayurvedic treatments, in both IP and OP level to evaluate its effect in the functional improvement. The study period was totally 57 days which included 21 days each at inpatient and outpatient basis and 15 days of follow up. Initially Sathaila Shastika Pinda Sweda was done for first 7 days followed by Takradhara for another 7 days. Consecutively Abhyanga with Pinda taila and Thalam with Amalaki were done for next 7 days. Then treatment was done on OP basis with internal medicines. Result: Results shows that the prescribed Ayurvedic treatments helped to control the progressive signs and symptoms. The quality of life and range of movements of the affected joints improved. Major difference showing a good improvement in carrying out the day today life activities was noted. Conclusion: Traditional Ashtavaidyan Ayurveda therapy is found effective in controlling the progressive symptoms of patients and improvement in functional ability of the patients with SLE. More over there was no adverse drug reaction recorded during as well there was significant change observed in liver and renal function tests. This indicates that the therapy is safe without producing any complication or side effects.